2006
DOI: 10.2174/157340106778017896
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Dietary Fibres with the Colon

Abstract: The term dietary fibre describes a wide range of highly divergent (mainly polysaccharide) compounds that escape digestion before the colon. Fibre is often regarded as a neutral dietary compound, not interacting with the gut and only offering dietary "benefit" by the consequent absence of calorific macronutrients, or by bulking out luminal content.Although the above benefits are apparent, a number of other physiological effects of dietary fibres in the colon have previously been described. This review outlines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 217 publications
(287 reference statements)
0
13
0
2
Order By: Relevance
“…More folds in the colon would result in increases in the propulsive force, increasing rate of bolus passage along the colon. The increasing fiber content in leaf meal based diets is likely to have stimulated colon motility (Staniforth, Baird, Fowler, & Lister, 1991;Brownlee, Dettmar, Strugala, & Pearson, 2006;Zeng, Lazarova, & Bordonaro, 2014) resulting in increases in the number of colon folds. Such segmental contractions result in increased water absorption and electrolyte exchange (Maykel & Opelka, 2004) and possibly reduced contact time between digesta and intestinal lumen.…”
Section: Discussmentioning
confidence: 99%
See 1 more Smart Citation
“…More folds in the colon would result in increases in the propulsive force, increasing rate of bolus passage along the colon. The increasing fiber content in leaf meal based diets is likely to have stimulated colon motility (Staniforth, Baird, Fowler, & Lister, 1991;Brownlee, Dettmar, Strugala, & Pearson, 2006;Zeng, Lazarova, & Bordonaro, 2014) resulting in increases in the number of colon folds. Such segmental contractions result in increased water absorption and electrolyte exchange (Maykel & Opelka, 2004) and possibly reduced contact time between digesta and intestinal lumen.…”
Section: Discussmentioning
confidence: 99%
“…Such segmental contractions result in increased water absorption and electrolyte exchange (Maykel & Opelka, 2004) and possibly reduced contact time between digesta and intestinal lumen. This is important as it reduces colon mucosal exposure to potential damaging agents of either endogenous or exogenous origin (Brownlee et al, 2006) while allowing the colon to absorb as much water as is possible.…”
Section: Discussmentioning
confidence: 99%
“…In this context, it was reported that the higher consumption of diet rich in grains and vegetables decreases the incidence of CRC. This effect involves different mechanisms such as the diminution in the fecal transit time due to the increase in the stool bulk, and consequently, it reduces the contact of carcinogen with colon cells and the fermentation of these fibers of colonic components [14,32]. In addition, significant reduction in concentration of acetate, propionate, and butyrate with increase in fecal pH [33] and the decrease in the number of obligate anaerobe microorganisms have been reported in individuals with colon cancer [34] when compared with healthy people.…”
Section: Ibd Complications and Microbiota Manipulationmentioning
confidence: 99%
“…The role of dietary fibre in the body is physiological one and not chemical one, due their functional properties and their effect on the gastrointestinal tract (GI) which improves the gut motility, but also on chemical and bacteriological changes that occur in the intestine (Brownlee et al, 2006;Burkitt et al, 1974). There are two ways in which dietary fiber favors the gut motility; first is their capacity to hold water which contribute to fecal bulk, increamenting stool mass and therefore intestinal luminal bulk due to water retention of dietary fiber increasing persitalsis (Dello Staffolo et al, 2012).…”
Section: Beneficial Health Effects Of Dietary Fibermentioning
confidence: 99%